2014
DOI: 10.1371/journal.pone.0112059
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationships of Novel Salicylaldehyde Isonicotinoyl Hydrazone (SIH) Analogs: Iron Chelation, Anti-Oxidant and Cytotoxic Properties

Abstract: Salicylaldehyde isonicotinoyl hydrazone (SIH) is a lipophilic, tridentate iron chelator with marked anti-oxidant and modest cytotoxic activity against neoplastic cells. However, it has poor stability in an aqueous environment due to the rapid hydrolysis of its hydrazone bond. In this study, we synthesized a series of new SIH analogs (based on previously described aromatic ketones with improved hydrolytic stability). Their structure-activity relationships were assessed with respect to their stability in plasma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The selected compounds allowed comparison of binding groups with (S,N,S) and (S,N,O) donor sets, as well as different functional groups (e.g., aroyl hydrazones vs semicarbazones within the (S,N,O) binding units). In addition, methyl hydrazone analogs were included because studies on SIH and related high-affinity hydrazone chelators indicated that these derivatives are more stable with respect to hydrolytic degradation [42].…”
Section: Resultsmentioning
confidence: 99%
“…The selected compounds allowed comparison of binding groups with (S,N,S) and (S,N,O) donor sets, as well as different functional groups (e.g., aroyl hydrazones vs semicarbazones within the (S,N,O) binding units). In addition, methyl hydrazone analogs were included because studies on SIH and related high-affinity hydrazone chelators indicated that these derivatives are more stable with respect to hydrolytic degradation [42].…”
Section: Resultsmentioning
confidence: 99%
“…The fluorimetric calcein-AM assay was performed by established methods, as described previously [ 38 , 39 ]. The Fe chelation efficiency of the metabolites in cells was expressed as a percentage of that of the parent chelator, Dp44mT or DpC (100%).…”
Section: Methodsmentioning
confidence: 99%
“…The Fe chelation efficiency of the metabolites in cells was expressed as a percentage of that of the parent chelator, Dp44mT or DpC (100%). For studies assessing the ability of these agents to induce 59 Fe mobilization and inhibit 59 Fe uptake from 59 Fe-transferrin by cells, human transferrin (Sigma-Aldrich, Germany) was labeled with 59 Fe (PerkinElmer, MA, USA) to generate 59 Fe-transferrin at a final specific activity of 500 pCi/pmol Fe, as previously described [ 22 , 39 , 40 ]. The unbound 59 Fe was removed by exhaustive vacuum dialysis against a large excess of 0.15 M NaCl buffered to pH 7.4 with 1.4% NaHCO 3 by standard methods [ 22 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…4-(2-Fluorophenoxy)quinolineacylhydrazones showed excellent antiproliferative activity and c-Met kinase inhibitory activity [13]. Salicylaldehyde isonicotinoylhydrazone analogs behaved as iron chelators especially in MCF-7 breast adenocarcinoma cells and this was correlated to their cytotoxic activity [14], while salicylaldehyde 1-arylmethyl-3-aryl-1 H -pyrazole-5-carbohydrazide hydrazone derivatives inhibited the growth of A549 lung cancer cells [15]. We have previously reported on 2-arylamino-6-trifluoromethyl-3-(hydrazinocarbonyl)pyridines [16] showing in vitro inhibitory activity against human tumour cell lines at low micromolar to nanomolar concentrations.…”
Section: Introductionmentioning
confidence: 99%